Surface Modifications for Zirconia Dental Implants: A Review - Sun, Lu; Hong, Guang (Frontiers in Dental Medicine, 2021)
Zirconia-based bioceramic is a potential material for dental implants developed and introduced in dentistry 30 years ago. However, some limitations still exist for zirconia implants caused by several factors, such as manufacturing difficulties, low-temperature degradation (LTD), long-term stability, and clinical experience. Several studies validated that some subtle changes on the zirconia surface might significantly impact its mechanical properties and osseointegration. Thus, attention was paid to the effect of surface modification of zirconia implants. This review generally summarizes the surface modifications of zirconia implants to date classified as physical treatment, chemical treatment, and surface coating, aiming to give an overall perspective based on the current situation. In conclusion, surface modification is an effective and essential method for zirconia implant application. However, before clinical use, we need more knowledge about these modification methods.